Junie B. Jones loves handsome Warren - Park, Barbara; Brunkus, Denise (New York Random House, 1996)
Unable to compete with her friends' fancy clothes and running ability, irrepressible six-year-old Junie B. finds her own way to make the new boy at school like her.
F
"A first stepping stone book."
310
F
Keywords: Friendship -- Fiction; Kindergarten -- Fiction; Schools -- Fiction